Afirmasi PDN (Produk dalam Negri) dan Produk Lokal dalam Efektivitas Kebijakan Pengadaan di Pemerintah Kabupaten Bangkalan - Mohammad Jainuri Jayanto; Widyawati Widyawati; Nihayatus Sholichah; Ika Devy Pramudiana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study examines the implementation and effectiveness of the domestic product affirmation (pdn) and local product policies in bangkalan regency. Despite the strong legal framework established by national regulations such as presidential regulation no. 12/2021 and presidential instruction no. 2/2022, the realization of these policies faces significant challenges at the local level. The research identifies critical barriers, including the mismatch between supply and demand, limited product certification, and inadequate capacity of local micro, small, and medium enterprises (msmes) to meet quality and compliance standards. Furthermore, the study reveals that the low awareness and commitment among procurement officials, combined with administrative delays and insufficient supervision, hamper the achievement of target procurement goals, such as allocating at least 40% of government expenditure to local and msme products. Data collected through interviews, participant observations, and document analysis highlight that strengthening local msmes’ capacity, improving product quality standards, facilitating certification processes, and fostering stakeholder collaboration are essential strategies for optimizing the policy’s impact. The findings suggest that a comprehensive, multidimensional approach involving capacity building, standardization, policy enforcement, and continuous monitoring is critical to realizing the full potential of pdn and local product affirmation policies. Ensuring an effective synergy among government agencies, industry players, and oversight institutions can significantly enhance local economic growth, promote regional self-reliance, and improve the welfare of the local community. This study underscores the importance of targeted interventions and supportive mechanisms to turn policy aspirations into tangible development outcomes in bangkalan and similar regions.